International business - Wall, Stuart , 1946-; Minocha, Sonal; Rees, Bronwen (Prentice Hall Financial Times, 2010)
International Businessprovides a clear and concise introduction to the environment and functions of international business. ?nbsp;It explains in straightforward language the economic and financial underpinnings of international trade, the more subtle organisational and cultural issues, and the managerial challenges which face organisations of all types and sizes. In particular, it provides up-to-the-minute coverage of recent global events - the economic downturn and uncertainty in financial markets.It is written for students on undergraduate and postgraduate degree programmes, or undertaking professional qualifications. It is especially suitable for non-specialist students of business.